Case report: Bilateral total knee replacement in severe knee osteoarthritis - Anwarali Khan, Mohammed Harris; Zulkifly, Ahmad Hafiz; Noor Rahin, Mohd. Shahidan (2016)
Introduction 40 years old malay gentleman with underlying gout and hyper tension presented with chief complaint of bilateral knee pain for 10 years duration. He was walking with limping gait and unable to squat or sit cross legs. Pain had been increasing for the last 5 years. He was dependent on analgesia. Since pain was worsening patient was on wheelchair ambulation. On examination patient right knee, no swelling, fixed flexion at 10 degree, range of movement 10-100 degree flexion, lateral collateral laxity and varus deformity. Left knee had fixed flexion at 5 degree, range of movement 5-100 degree and varus deformity. Blood investigation showed uric acid. Xray of bilateral knee showed reduced joint space, and sclerotic bone.